Uncovering the Secrets of Motion: A Literature Review of Lagrange and Newtonian Mechanics - Wulandari, Anggres; Setiaji, Bayu (CV. Rayyan Dwi Bharata, 2024)
Physics is a branch of natural science. Since ancient times, humans have been interested in the movement of objects around them and motion is an area studied in mechanics. This research aims to understand the principles of mechanics in Lagrange and Newtonian mechanics for solving motion problems and their applications. The method used is the literature review method. Literature is a comprehensive overview of previous research on a particular topic. Literature review is a systematic process for identifying, evaluating, and synthesizing previously published scientific works on a particular topic. There are 20 sources used, consisting of books and scientific journals. The research results show that motion is an object that experiences movement from one place to another. Problems of motion of objects can be solved using the laws and principles of Newtonian and Lagrange mechanics. Lagrange mechanics is used to solve complex problems that cannot be solved with Newtonian mechanics. Lagrange mechanics focuses on the forces that cause objects to move, while Newtonian mechanics focuses on the energy that causes objects to move.